Identificação de ilhas de calor urbano em cidade de porte médio: proposta metodológica adaptada às zonas climáticas locais – ZCLs - Megda, Otávio Reis (2020)
Urban spaces, growing in verticalized and waterproofed structures, have become increasingly common among cities, configuring themselves as dense over-built areas, with a high variability in the climatic pattern resulting from physical configurations, often chaotic. Since the 1990s, with advances in the specific geotechnological sector, the demand for analyzes in urban climate has increased significantly. Therefore, the methodological proposal for the use of an unmanned aerial vehicle (UAV) or “drone” expressing an adequacy in the analysis scenario in the area. In this research, an aggregating methodology is proposed, at the pedestrian level, with a thermometer and, with the use of an vant, vertical temperature measurements in different strata (30, 60 and 75 meters high), applying the data within the concept of Local Climate Zones – LCZs, proposed by Stewart and Oke (2012), in order to better understand the different compositions of urban heat islands in spaces with different levels of land occupation, as well as their physical components. Therefore, this work analyzes the LCZs in Franca, in the state of São Paulo, from the perspective of the formation of the heat island on the vertical scale, showing how far the city air is compromised, and can assist several researches in the nature of planning and territorial ordering. The data showed the formation of the urban heat island not only at the pedestrian level, but at points up to 75 meters high in summers and favorable synoptic conditions, as well as some points with freshness islands of within the urban area. The winter periods of 2017 and 2018 made evident a thermal variation of 2.9ºC in the analyzed route, with few significant differences in the different heights, while the summer periods of 2018 and 2019 showed a thermal variation of 7.9ºC at the pedestrian level, and at 30 meters high, values of 17ºC, which shows the formation of the urban heat island in the Urban canopy layer